Occurrence and Characterization of Salmonella Isolated From Chicken Breeder Flocks in Nine Chinese Provinces - Song, Yan; Wang, Fangkun; Liu, Yang; Song, Yanying; Zhang, Lin; Zhang, Fuyou; Gu, Xiaoxue; Sun, Shuhong (Frontiers in Veterinary Science, 2020)
We investigated the prevalence of salmonellosis on 17 poultry breeding farms in nine Chinese provinces (Shandong, Jiangsu, Anhui, Zhejiang, Fujian, Guangdong, Yunnan, Sichuan, and Chongqing). Altogether, 3508 samples from poultry breeding farms were collected in 2019, including 1400 from cloaca swabs, 210 from feed, 1688 from chicken embryos, and 210 from water. All the samples were subjected to bacterial isolation and culture, and bacterial species were identified by polymerase chain reaction. Serotyping, multilocus sequence typing (MLST), and drug-resistance phenotyping were performed on the isolates identified as Salmonella. Altogether, 126 Salmonella strains were detected in the 3508 samples and the positivity rate for the samples was 3.59%. Among all the strains, 95 Salmonella isolates were selected for antimicrobial susceptibility test, resistance gene detection, serotyping and genotyping. S. gallinarum-pullorum (57/95, 60.00%), S. enteritidis (22/95, 23.16%), and S. agona (16/95, 16.84%) serotypes were identified. The MLST classification showed that the 95 Salmonella strains fell into the following five sequence types (STs): ST92 (37/95, 38.95%), ST11 (22/95, 23.16%), ST2151 (19/95, 20.00%), ST13 (16/95, 16.84%), and ST470 (1/95, 1.05%). Apart from ST13, the other four STs shared close genetic relationships, and the genetic direction was ST11-ST470-ST92-ST2151. The resistance rates in the 95 isolates were 100% (95/95) for erythromycin, 68.42% (65/95) for tetracycline, and 53.68% (51/95) for streptomycin and ampicillin respectively. The isolates were sensitive to polymyxin and sulfamethoxazole. Multi-drug resistance was seen in 70.53% (67/95) of the isolates. β-lactam-, aminoglycoside- and sulfonamide-encoding resistance genes were detected by PCR. The detection rate for blaTEM and sul3 was 100% (95/95), whereas sul2 and aaC4 had rates of 52.63% and 23.16%, respectively. These results indicate that some of the salmonellosis seen in Chinese breeding chicken farms may be caused by infection with S. gallinarum-pullorum, S. enteritidis, and S. agona. They also show that some Salmonella isolates have multi-drug resistance phenotypes and carry multi-drug resistance genes.